NARASI PENDERITAAN DAN KESABARAN NABI DALAM YAKOBUS 5:10: IMPLIKASI TEOLOGIS BAGI KEPEMIMPINAN GEMBALA JEMAAT - Paulus Kunto Baskoro; Anon Dwi Saputra (Sekolah Tinggi Teologi Arastamar Bengkulu, 2026)
Pastors are often perceived as problem solvers, yet they are ordinary individuals carrying a sacred calling that demands complete spiritual exemplary. A crucial, often overlooked focus is the perseverance in enduring unexpressed internal suffering. This descriptive qualitative study, utilizing a library research method, aims to analyze the relevance of James 5:10 for contemporary ecclesiastical leadership. Through the exegesis of the text